INVESTIGATING THE EFFECT OF SLUDGE/CLAY RATIO AND FIRING TEMPERATURE ON THE COMPRESSION STRENGTH AND WATER ABSORPTION CAPACITY OF BRICK USING RESPONSE SURFACE METHODOLOGY - Gebremedhin, Tsegay; Kebede, Shimelis; Kiflie, Zebene (Zede Journal of Ethiopian Engineers and Architects, 2023)
Presently, the sludge generated from the Zero Liquid Discharge (ZLD) facility in Hawassa Industrial Park is collected inside a nearby big constructed shed without any treatment. This study investigated the utilization of this textile sludge as input for the production of brick construction material as the sludge management tool. The study focused on finding optimum parameters for the production of bricks using response surface methodology. The proportion of sludge mix and the firing temperature were selected as the study independent parameters with the compressive strength and water absorption as the experimental responses. Based on the analysis of variance (ANOVA), linear and quadratic model equations were selected for compressive strength and water absorption capacity, respectively. The regression analyses have shown that the model equations ware satisfactory enough to predict the selected responses within the experimental range with 94.98 % and 99.71 % variability in the same order. Based on numerical optimization, a sludge mix of 18.66 % and a temperature of 1000oC were selected as optimum synthesis parameters predicting bricks with 3.5 MPa comprehensive strength and 16 % water absorption. Key words: Statistical Optimization, textile sludge, bricks, zero liquid discharge.